Utilization of the Maternal and Child Health Handbook in Early Identification of Autism Spectrum Disorder and Other Neurodevelopmental Disorders. Issue 3 (29th November 2020) - Hirota, Tomoya; Bishop, Somer; Adachi, Masaki; Shui, Amy; Takahashi, Michio; Mori, Hiroyuki; Nakamura, Kazuhiko
Abstract : There is relatively little information about prospectively reported developmental milestones from caregivers of children who go on to be diagnosed with neurodevelopmental disorders (NDDs), including autism spectrum disorder (ASD). The current study examined rates of early skill attainment in 5‐year‐old children who participated in a comprehensive in‐person assessment for NDDs in Hirosaki in Japan. Developmental milestone data were extracted from their Maternal and Child Health Handbook (MCHH), a booklet distributed to all pregnant women as part of universal health care. Seven hundred and twenty children underwent the assessment, among whom 455 received one or more NDD diagnoses (ASD: n = 124, non‐ASD NDD: n = 331). Developmental skills were organized into four domains (motor, social interaction, communication, self‐help), and the cumulative number of potential delays in each domain was calculated for each participant within three different age ranges (by 12 months, by 24 months, and by 36 months). Even by age 12 months, children with ASD/NDDs showed more potential delays across domains compared to those who received no NDD diagnosis. However, differences between those with ASD and those with non‐ASD NDDs were not apparent until 24 months for social interaction and communication, and 36 months for self‐help. These findings provide insights into specific behaviors that could be used to screen for ASD and other NDDs. In addition, the present study indicates the potential utility of the MCHH as a broadband screening tool to educate parents about what to look for in charting their child's early development. Lay Summary: The present study examined prospectively charted developmental milestones from home‐based records used as part of universal health care in 720 5‐year‐old children from Hirosaki, Japan. All children participated in a comprehensive evaluation to determine if they met criteria for a neurodevelopmental disorder (NDD), including autism spectrum disorder (ASD). Compared to those who received no NDD diagnosis, children with NDDs exhibited higher rates of potential delays across developmental domains, including social interaction, communication, and self‐help. For some children, these delays were apparent before the age of 12 months. Differences between diagnostic groups became even more pronounced by 24 and 36 months, well before the average age of diagnosis. This suggests that home‐based records can be useful tools to educate caregivers about what to look for in charting their child's early development and could assist with early screening efforts.